Prospective study of oral anticoagulants and risk of liver injury in patients with atrial fibrillation. Issue 11 (5th January 2017) - Alonso, Alvaro; MacLehose, Richard F; Chen, Lin Y; Bengtson, Lindsay GS; Chamberlain, Alanna M; Norby, Faye L; Lutsey, Pamela L
Abstract : Objective: To assess the risk of liver injury hospitalisation in patients with atrial fibrillation (AF) after initiation of direct oral anticoagulants (DOACs) or warfarin and to determine predictors of liver injury hospitalisation in this population. Methods: We studied 113 717 patients (mean age 70, 39% women) with AF included in the MarketScan Commercial and Medicare Supplemental databases with a first prescription for oral anticoagulation after 4 November 2011, followed through 31 December 2014. Of these, 56 879 initiated warfarin, 17 286 initiated dabigatran, 30 347 initiated rivaroxaban and 9205 initiated apixaban. Liver injury hospitalisation and comorbidities were identified from healthcare claims. Results: During a median follow-up of 12 months, 960 hospitalisations with liver injury were identified. Rates of liver injury hospitalisation (per 1000 person-years) by oral anticoagulant were 9.0 (warfarin), 4.0 (dabigatran), 6.6 (rivaroxaban) and 5.6 (apixaban). After multivariable adjustment, liver injury hospitalisation rates were lower in initiators of DOACs compared with warfarin: HR (95% CI) of 0.57 (0.46 to 0.71), 0.88 (0.75 to 1.03) and 0.70 (0.50 to 0.97) for initiators of dabigatran, rivaroxaban, and apixaban, respectively (vs. warfarin). Compared with dabigatran initiators, rivaroxaban initiators had a 56% increased risk of liver injury hospitalisation (HR 1.56, 95% CI 1.22 to 1.99). In addition to type of anticoagulant, prior liver, gallbladder and kidney disease, cancer, anaemia, heart failure and alcoholism significantly predicted liver injury hospitalisation. A predictive model including these variables had adequate discriminative ability (C-statistic 0.67, 95% CI 0.64 to 0.70). Conclusions: Among patients with non-valvular AF, DOACs were associated with lower risk of liver injury hospitalisation compared with warfarin, with dabigatran showing the lowest risk.